Handbook of software quality assurance - Schulmeyer, G. Gordon (Artech House, 2008)
This thoroughly revised fourth edition of the popular book, Handbook of Software Quality Assurance, brings together the latest SQA (software quality assurance) methods, recognizing the importance of CMMI® and the ISO 900-3 standard. This unique book offers you a wide spectrum of experiences and issues presented in papers from leading experts in SQA, DQA (development quality assurance), and software development and management. The fourth edition is a significant update to past editions, bringing you the very latest on current best practices in the field. You learn the role of SQA/DQA with regard to ISO 9001-2000 requirements and the criteria from the Software Engineering Institute for the various levels of CMMI®. You also find an updated discussion on the American Society for Quality (ASQ) SQA certification program, covering the benefits of becoming an ASQ certified software quality engineer. This practical resource shows you how to move an organization from CMMI® software quality assurance compliance to developmental quality assurance compliance. The book covers the commercial standards and modern development methods of SQA and DQA, and details how SQA can be implemented in organizations large and small. This volume also helps you better understand the requirements of the ASQ's CSQE examination. From quality management concepts for IT, teaching SQA in an industrial environment, and the inspection process, to the impact of SQA certification on the hiring process, software quality metrics recommendations, and software reliability, this invaluable book serves as your a one-stop resource for complete and current software quality assurance knowledge. Publisher abstract.
Keywords: Computer software -- Quality control.; elektronické knihy; electronic books